Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To find the equation of a line that is parallel to [tex]\(-2x + 3y = -6\)[/tex] and passes through the point [tex]\((-2, 0)\)[/tex], follow these steps:
1. Determine the slope of the given line:
The given equation of the line is [tex]\(-2x + 3y = -6\)[/tex].
To find the slope, we first convert this equation to the slope-intercept form [tex]\( y = mx + b \)[/tex], where [tex]\( m \)[/tex] is the slope.
[tex]\[ -2x + 3y = -6 \][/tex]
Solve for [tex]\( y \)[/tex]:
[tex]\[ 3y = 2x - 6 \][/tex]
[tex]\[ y = \frac{2}{3}x - 2 \][/tex]
So, the slope [tex]\( m \)[/tex] of the given line is [tex]\(\frac{2}{3}\)[/tex].
2. Construct the equation of the new line:
Since parallel lines have the same slope, the slope of the new line is also [tex]\(\frac{2}{3}\)[/tex].
Use the point-slope form of the equation of a line, [tex]\( y - y_1 = m(x - x_1) \)[/tex], where [tex]\( (x_1, y_1) \)[/tex] is the point the line passes through.
Given point [tex]\((-2, 0)\)[/tex]:
[tex]\[ y - 0 = \frac{2}{3}(x - (-2)) \][/tex]
Simplify the equation:
[tex]\[ y = \frac{2}{3}(x + 2) \][/tex]
3. Convert the equation to the standard form:
Expand and simplify the above equation:
[tex]\[ y = \frac{2}{3}x + \frac{4}{3} \][/tex]
To eliminate the fraction, multiply through by 3:
[tex]\[ 3y = 2x + 4 \][/tex]
Rearrange to the standard form [tex]\( Ax + By = C \)[/tex]:
[tex]\[ 2x - 3y = -4 \][/tex]
Thus, the equation of the line that is parallel to [tex]\(-2x + 3y = -6\)[/tex] and passes through the point [tex]\((-2, 0)\)[/tex] is:
[tex]\[ 2x - 3y = -4 \][/tex]
1. Determine the slope of the given line:
The given equation of the line is [tex]\(-2x + 3y = -6\)[/tex].
To find the slope, we first convert this equation to the slope-intercept form [tex]\( y = mx + b \)[/tex], where [tex]\( m \)[/tex] is the slope.
[tex]\[ -2x + 3y = -6 \][/tex]
Solve for [tex]\( y \)[/tex]:
[tex]\[ 3y = 2x - 6 \][/tex]
[tex]\[ y = \frac{2}{3}x - 2 \][/tex]
So, the slope [tex]\( m \)[/tex] of the given line is [tex]\(\frac{2}{3}\)[/tex].
2. Construct the equation of the new line:
Since parallel lines have the same slope, the slope of the new line is also [tex]\(\frac{2}{3}\)[/tex].
Use the point-slope form of the equation of a line, [tex]\( y - y_1 = m(x - x_1) \)[/tex], where [tex]\( (x_1, y_1) \)[/tex] is the point the line passes through.
Given point [tex]\((-2, 0)\)[/tex]:
[tex]\[ y - 0 = \frac{2}{3}(x - (-2)) \][/tex]
Simplify the equation:
[tex]\[ y = \frac{2}{3}(x + 2) \][/tex]
3. Convert the equation to the standard form:
Expand and simplify the above equation:
[tex]\[ y = \frac{2}{3}x + \frac{4}{3} \][/tex]
To eliminate the fraction, multiply through by 3:
[tex]\[ 3y = 2x + 4 \][/tex]
Rearrange to the standard form [tex]\( Ax + By = C \)[/tex]:
[tex]\[ 2x - 3y = -4 \][/tex]
Thus, the equation of the line that is parallel to [tex]\(-2x + 3y = -6\)[/tex] and passes through the point [tex]\((-2, 0)\)[/tex] is:
[tex]\[ 2x - 3y = -4 \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.